The Study of C3H6 Impact on Selective Catalytic Reduction by Ammonia (NH3-SCR) Performance over Cu-SAPO-34 Catalysts - Yingfeng Duan (MDPI AG, 2021)
In present work, the catalytic performance of Cu-SAPO-34 catalysts with or without propylene during the NH3-SCR process was conducted, and it was found that the de-NOx activity decreased during low temperature ranges (<350 °C), but obviously improved within the range of high temperatures (>350 °C) in the presence of propylene. The XRD, BET, TG, NH3-TPD, NOx-TPD, in situ DRIFTS and gas-switch experiments were performed to explore the propylene effect on the structure and performance of Cu-SAPO-34 catalysts. The bulk characterization and TG results revealed that neither coke deposition nor the variation of structure and physical properties of catalysts were observed after C3H6 treatment. Generally speaking, at the low temperatures (<350 °C), active Cu2+ species could be occupied by propylene, which inhibited the adsorption and oxidation of NOx species, confining the SCR reaction rate and causing the deactivation of Cu-SAPO-34 catalysts. However, with the increase of reaction temperatures, the occupied Cu2+ sites would be recovered and sequentially participate into the NH3-SCR reaction. Additionally, C3H6-SCR reaction also showed the synergetic contribution to the improvement of NOx conversion at high temperature (>350 °C).